SAT0454 In primary sjÖgren's syndrome blood cd180-negative b cells are increased in patients with high systemic disease activity. (12th June 2018) - Felten, R.; Mayeur-Rousse, C.; Miguet, L.; Arnaud, L.; Chatelus, E.; Javier, R.-M.; Petit, H.; Sibilia, J.; Sordet, C.; Fornecker, L.; Mauvieux, L.; Gottenberg, J.-E.
Abstract : Background: CD180, a related member of the Toll-like receptor family, seems to be underexpressed at the plasma membrane in circulating B cells of auto-immune disease (systemic lupus especially), 1 and is lost in various B-cell lymphomas except marginal zone lymphomas (MZL), the most severe complication of primary Sjögren's Syndrome (pSS). 2 Objectives: To define the expression of CD180 at the plasma membrane of circulating B cells of pSS and determine its association with systemic disease activity. Methods: The expression of CD180 at the plasma membrane of circulating B cells was studied by flow cytometry, in 69 successive patients with pSS, in comparison to patients with systemic lupus (SLE) (n=7) and healthy controls (n=28). Results: The cohort of pSS was composed of 65 women for 4 men, median age of 59 years. 25–89 Median clinESSDAI was 2 [0–18], 46 patients with a clinESSDAI >0 (low disease activity), 18 patients with a clinESSDAI >5 (moderate disease activity) and 6 patients≥14 (high disease activity). The more frequently involved domains of the ESSDAI were biological (39%, n=27), glandular (32%, n=22), articular (20%, n=14), and peripheral neurological (9%, n=6) domains. Fourty patients were anti-SSA+, 16 anti-SSA and anti-SSB+. 18 had a hypergammaglobulinemia, 17 a hypocomplementemia, 7 a cryoglobulinemia, 18 a rheumatoid factor and 9 a lymphopenia. - CD180-negative B cells in pSS, SLE and controls The proportion of total lymphocytes, B cells, T cells, NK cells or CD180-negative B cells (0.85% vs 0.95%, p=0.64) was not significantly different between pSS patients and healthy controls. Patients with SLE had significantly fewer lymphocytes (860 vs 1544, p=0.0012), B cells and T cells than those with pSS (p=0.023 and p=0.0016); CD180-negative B cells tended have a higher proportion in SLE than in pSS patients (1.9% vs 0.85%, p=0.055). - Increase of CD180-negative B cells in patients with pSS and high systemic disease activity CD180-negative B cells subset was significantly higher in patients with high systemic disease activity (2.55% CD180-negative B cells in patients with clinESSDAI ≥14 vs 0.8% in patients with clinESSDAI <14, p=0.036). CD180-negative B cells subset was also significantly higher in patients with anti-SSA and anti-SSB+ (1.9% vs 0.8%, p=0.0082) and in patients with markers of B-cell activation: hypergammaglobulinemia (1.7% vs 0.75%, p=0.034), hypocomplementemia (2.1% vs 0.8%, p=0.0021), cryoglobulinemia (4.6% vs 0.8%, p=0.0097), presence of rheumatoid factor (1.7% vs 0.7%, p=0.015). Conclusions: Blood CD180-negative B cells are increased in pSS patients with high systemic disease activity or in immunologically active pSS. Fonctionnality of CD180 and the prognostic interest of CD180 staining on blood B cells to predict lymphoma in pSS patients, have now to be studied. Reference: [1] Kikuchi Y, et al. RP105-negative B cells in patients with Sjögren's syndrome. [2] Mayeur-Rousse C, et al. CD180 expression in B-cell lymphomas: A multicenter GEIL study. Disclosure of Interest: None declared